Household final energy footprints in Nepal, Vietnam and Zambia: composition, inequality and links to well-being - Marta Baltruszewicz; Julia K Steinberger; Diana Ivanova; Lina I Brand-Correa; Jouni Paavola; Anne Owen (Environmental Research Letters, 2021)
The link between energy use, social and environmental well-being is at the root of critical synergies between clean and affordable energy (SDG7) and other Sustainable Development Goals (SDGs). Household-level quantitative energy analyses enable better understanding regarding interconnections between the level and composition of energy use, and SDG achievement. This study examines the household-level energy footprints in Nepal, Vietnam, and Zambia. We calculate the footprints using multi-regional input–output with energy extensions based on International Energy Agency data. We propose an original perspective on the links between household final energy use and well-being, measured through access to safe water, health, education, sustenance, and modern fuels. In all three countries, households with high well-being show much lower housing energy use, due to a transition from inefficient biomass-based traditional fuels to efficient modern fuels, such as gas and electricity. We find that households achieving well-being have 60%–80% lower energy footprint of residential fuel use compared to average across the countries. We observe that collective provisioning systems in form of access to health centers, public transport, markets, and garbage disposal and characteristics linked to having solid shelter, access to sanitation, and minimum floor area are more important for the attainment of well-being than changes in income or total energy consumption. This is an important finding, contradicting the narrative that basic well-being outcomes require increased income and individual consumption of energy. Substantial synergies exist between the achievement of well-being at a low level of energy use and other SDGs linked to poverty reduction (encompassed in SDG1), health (SDG3), sanitation (SDG6), gender equality (SDG5), climate action and reduced deforestation (SDG 13 and SDG15) and inequalities (SDG10).